Human Resource management practices in small organisations in the event and exhibition industry in Cape Town, and how these practices contribute to organisational performance - Putter, Anneke (Organisational Psychology, 2017)
This study aims to explore how human resource management (HRM) practices are implemented in small organisations in the event and exhibition industry in Cape Town, and to examine to what extent these practices influence these organisations' organisational performance. The researcher followed a qualitative case study research design and utilised a semi-structured interview and Likert scale survey. A review of current academic literature has revealed that small organisations, functioning within a highly pressurised environment, focus more on operational survival than on the organisational management of human resources (HR). The event and exhibition industry in Cape Town is characterised by short bursts of high pressurised projects, with fixed deadlines, high profile clients and intense, irregular work periods. Taking into account the aforementioned factors, it is therefore paramount to examine how these small organisations understand HRM practices, as well as how said practices are implemented amidst the challenges experienced in this industry. Overall, the results suggest a positive association between the prioritisation of HRM practices, the alignment of HRM practices to the business plan and the successful implementation of HRM practices in the ten organisations that participated in this study.